In Situ Generated Novel 1H MRI Reporter for β-Galactosidase Activity Detection and Visualization in Living Tumor Cells - Gao, Shuo; Zhao, Lei; Fan, Zhiqiang; Kodibagkar, Vikram D.; Liu, Li; Wang, Hanqin; Xu, Hong; Tu, Mingli; Hu, Bifu; Cao, Chuanbin; Zhang, Zhenjian; Yu, Jian-Xin (Frontiers in Chemistry, 2021)
For wide applications of the lacZ gene in cellular/molecular biology, small animal investigations, and clinical assessments, the improvement of noninvasive imaging approaches to precisely assay gene expression has garnered much attention. In this study, we investigate a novel molecular platform in which alizarin 2-O-β-d-galactopyranoside AZ-1 acts as a lacZ gene/β-gal responsive 1H-MRI probe to induce significant 1H-MRI contrast changes in relaxation times T1 and T2in situ as a concerted effect for the discovery of β-gal activity with the exposure of Fe3+. We also demonstrate the capability of this strategy for detecting β-gal activity with lacZ-transfected human MCF7 breast and PC3 prostate cancer cells by reaction-enhanced 1H-MRI T1 and T2 relaxation mapping.